Bibliography on the culturally disadvantaged. supplement iii - Harvard Univ., Cambridge, MA. Graduate School Of Education; Harvard Univ., Cambridge, MA. Graduate School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
This bibliography supplement lists material on various aspects of the culturally disadvantaged. Approximately 220 unannotated references are provided to documents dating from 1963 to 1966. Journals, books, and report materials are listed. Subject areas included are preschool programs, neighborhood development programs, short-term group counseling, rural youth, social change, and migrant children. (tc)
Contract Number: OEC-5-10-239.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Disadvantaged; Migrant Children; Neighborhood Improvement; Preschool Education; Rural Youth; Social Change; Cambridge